Reconstruction of Ethno-STEM Integrated Project Learning Models for Explanation of Scientific Knowledge Regarding Aroma Compounds of Indonesian and World Herbal Teas - Sudarmin, Sudarmin; Savitri, Erna Noor; Pujiastuti, Rr. S. E.; Yamtinah, Sri; Mohd Zaim, H. Hanim binti; Ariyatun (Jurnal Pendidikan IPA Indonesia, 2024)
The background to this research is the importance of finding an integration pattern between the project learning model and Ethno-STEM based inquiry to explain scientific knowledge regarding the aroma of herbal tea.  The fundamental research objective is to design an integration pattern for the project and Ethno-STEM learning model and reconstruct scientific knowledge based on public knowledge of the aromatic volatile compounds of Indonesian and world herbal teas. This research method and approach is mixed research. This qualitative approach is to find the integration of the project learning model and Ethno-STEM (Ethno-STEM PjLM) and its syntax. A quantitative approach regarding analyzing tea aroma volatile compounds using an Arduino gas sensor: research data from literature studies, interviews, reconstruction, and data on identifying volatile compounds in the aroma of herbal tea analyzed descriptively, qualitatively, and quantitatively. The results of the research concluded: (1) the reconstruction and integration pattern between PjLM Ethno-STEM is an integrated pattern with SUDARMIN syntax, (2) the reconstruction of scientific knowledge based on public knowledge regarding the process of isolation, extraction, and bioactivity of secondary metabolites, (3) herbal tea aroma volatiles compounds are identified by Arduino sensor: carbon dioxide, methane, propane, butane, acetone, alcohol, and ester, (4) the implementation of Ethno-STEM PjLM received a positive response from students.